Legal Protection for Buyers in Good Faith as a Result of the Cancellation of Transfer of Rights Based on a Court Decision - Kistriana, Farastya Enanggi; Purwadi, Hari; Nagara, Airlangga Surya (Journal of Legal and Cultural Analytics, 2025)
This study uses a normative legal research method with a case study approach, which is prescriptive and analytical in nature. It focuses on Supreme Court Decision Number 3507 K/Pdt/2023, where a bona fide buyer who acquired land rights through a valid sale before a PPAT and had a certificate in his name suffered losses due to the cancellation of the sale and purchase deed declared legally flawed. The results show that Indonesia’s land registration system adheres to a negative publication system with a positive tendency, so certificates do not guarantee ownership. The cancellation of rights creates legal uncertainty for bona fide buyers who meet the valid agreement requirements under Article 1320 KUHPerdata. Stronger legal protection is needed both preventively and repressively to achieve justice and legal certainty.